Suplementação de vitaminas E para tilápias do nilo ( Oreochromis niloticus) - Rodrigo Diana Navarro (2008)
Three experiments were conducted, as the first and second check the morphometry, cages, and performance, carcass quality with supplementation of vitamin E and the third with supplementation evaluate the performance of vitamin C. The researches were carried out in the experimental frog raising facilities at the DBA-UFV. All the experiments were randomly designed with five treatments (supplying 0, 50, 100, 150, and 200 mg/kg of vitamin E monophosphate) in an isoproteic ration with 36% CP and isocaloric with 3,600 kcal/kg of DE with four repetitions. In the first two experiments, the five levels of monophosphated vitamin E supplements were: 0, 50, 100, 150, and 200 mg/kg. In the third experiment, five levels of vitamin C (ascorbic acid monophosphate) supplements were used: 0, 50, 100, 150, and 200 mg/kg. In the first studyConsidering the weight of the gonad, gonadossomatic index, testes thickness and lumen percentage, significant differences (p<0.05) were observed for the treatment with 150mg/kg of vitamin E. The eicosapentaenoic fatty acid was statistically significant for the treatment without vitamin E. The fatty acids linoleicγ-linolenic α-linoleic and arachidonic increased in a quadratic way up to the estimated levels of 110mg, 111mg, 113mg, and 140 mg of vitamin E/kg of ration, respectively.Survivor rate increased in a quadratic way up to supplying 132 mg of vitamin C per kg of ration. Vitamin C supply did not influence carcass DM percentage. Similar results were observed for protein percentage in weight gain. It was not observed significant difference) for EE and fat percentage on weight gain. Vitamin C supplementation significantly influenced muscle glycogen concentration.